Design and fabrication of a thoracic phantom for radiation dose verification in mega-voltage X-ray beam. (2022) - Kumar, Lalit; Kishore, Vimal; Bhushan, Manindra; Kumar, Pawan; Kumar, Gourav
Abstract: To assess the radiological properties of racemosa wooden dust (RWD) and Poly (methyl methacrylate) (PMMA) for design and fabrication of a thoracic phantom for radiation dose verification in mega-voltage X-ray beam. The computed tomography images of RWD and PMMA were used to determine the radiological properties viz., Hounsfield units (HUs), relative electron density (RED) and mass density (MD). The estimated HUs, RED and MD were −828.2 ± 11.9, 0.172 ± 0.012, 0.150 ± 0.012 g/cc and 108.5 ± 7.3, 1.104 ± 0.004, 1.088 ± 0.005 g/cc for RWD and PMMA, respectively. The radiological properties of RWD and PMMA were in congruence with the value detailed in literature for lung tissue and muscle tissue of human body. Therefore, a phantom was design and fabricated using the combination of RWD and PMMA for radiation dose verification prior to radiation delivery to the cancer patients. The average deviation between dose computation engine and Ion-chamber estimations were within the stipulated tolerance (±3%). Thus, it was culminated that RWD and PMMA can be utilized for design and fabrication of phantom, which vindicates precise information about the quality assurance program for thoracic cancer patient treated using mega-voltage X-ray beam.